B-Cell Gene Therapy for Tolerance Induction: Host but Not Donor B-Cell Derived IL-10 is Necessary for Tolerance - Su, Yan; Zhang, Ai-Hong; Noben-Trauth, Nancy; Scott, David W. (Frontiers in Microbiology, 2011)
Genetically modified B cells are excellent tolerogenic APCs in multiple models of autoimmunity. However, the mechanisms of action are still not completely understood. In our models, we generate antigen-specific tolerogenic B cells by transducing naïve or primed B cells with an antigen-immunoglobulin G (peptide-IgG) construct. In order to be transduced, B cells require activation with mitogens such as LPS. We and others have found that LPS stimulation of B cells upregulates the production of IL-10, a key cytokine for maintaining immune tolerance. In the current study, we defined the role of B-cell produced IL-10 in tolerance induction by using IL-10 deficient B cells as donor APCs. We found that peptide-IgG transduced IL-10 KO B cells have the same effects as wt B cells in tolerance induction in an EAE model. Moreover, we demonstrated that the tolerogenic effect of peptide-IgG B cells was completely abrogated in anti-IL-10 receptor antibody treated recipients. Taken together, our results suggest that tolerance induced by peptide-IgG B-cell gene therapy requires IL-10 from the host but not donor B cells. These data shed important insights into the mechanisms of tolerance induction mediated by B-cell gene therapy.